2021
DOI: 10.3390/ijms222111701
|View full text |Cite
|
Sign up to set email alerts
|

Histone Modification in NSCLC: Molecular Mechanisms and Therapeutic Targets

Abstract: Lung cancer is the leading cause of cancer mortality in both genders, with non-small cell lung cancer (NSCLC) accounting for about 85% of all lung cancers. At the time of diagnosis, the tumour is usually locally advanced or metastatic, shaping a poor disease outcome. NSCLC includes adenocarcinoma, squamous cell carcinoma, and large cell lung carcinoma. Searching for novel therapeutic targets is mandated due to the modest effect of platinum-based therapy as well as the targeted therapies developed in the last d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 125 publications
(142 reference statements)
0
60
0
Order By: Relevance
“…The main genetic alterations affecting carcinogenesis involve changes in tumor suppressors (APC, p53 BRCA2, PTCH, NF1, VHL, Rb BCL2, SWI/SNF, p16, CD95, ST5, YPEL3, ST7, and ST14) and oncogenes (Ras, jun, fas, erbA, abl, raf, gsp, sis, erbB, and fms) in addition the onset and progression of oral cancer involve changes of DNA methylation, histone modifications, and non-coding alterations of RNA, including microRNAs (miRNA) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main genetic alterations affecting carcinogenesis involve changes in tumor suppressors (APC, p53 BRCA2, PTCH, NF1, VHL, Rb BCL2, SWI/SNF, p16, CD95, ST5, YPEL3, ST7, and ST14) and oncogenes (Ras, jun, fas, erbA, abl, raf, gsp, sis, erbB, and fms) in addition the onset and progression of oral cancer involve changes of DNA methylation, histone modifications, and non-coding alterations of RNA, including microRNAs (miRNA) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that HDACs overexpress in several cancers and appeared to have potential as therapeutic targets ( 18 ). HDAC overexpression can lead to TSG silencing or altered transcription by influencing genes encoding HAT enzymes or binding elements of HAT and HDAC enzymes, which are associated with carcinogenesis ( 13 ). Similarly, histone methyltransferases (HMTs) and histone demethylases (KDMs) regulate the histone methylation dynamically ( 74 ).…”
Section: Epigenetics In Nsclcmentioning
confidence: 99%
“…Several epigenetic therapies for NSCLC were carried out in clinical trials ( Table 1 ). Detecting the molecular characteristics of NSCLC subtypes, such as genetics and epigenetic variation, was critical for choosing the proper therapy for combination ( 13 ) while chemotherapy resistance was also found to be associated with epigenetic changes ( 188 ). Besides, DNA methylation is a double-sided procedure, unlike the changes of genetic information involving gene mutations or deletions.…”
Section: Epigenetics In the Innovative Diagnostic And Therapeutic Str...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer is a highly malignant tumor with the inherent biological properties of rapid proliferation and early spread, leading to a poor prognosis. Lung cancer is generally classified into two main histological types: small cell lung cancer and non‐small cell lung cancer (NSCLC), of which NSCLC accounts for approximately 85% of all cases 1–4 . Despite substantial progress in the treatment of NSCLC, including the advent of immunotherapy and various targeted therapies, the prognosis of patients with NSCLC remains poor and the 5‐year overall survival rate is still <19% 5–7 .…”
Section: Introductionmentioning
confidence: 99%